2015
DOI: 10.1186/s12889-015-1691-8
|View full text |Cite
|
Sign up to set email alerts
|

Under consumers’ scrutiny - an investigation into consumers’ attitudes and concerns about nudging in the realm of health behavior

Abstract: BackgroundNudging strategies have recently attracted attention from scholars and policy makers for their potential in influencing people’s behaviors on large scales. But is the fact that nudges do not forbid any choice-options or significantly alter people’s economic incentives sufficient to conclude that nudges should be implemented? While this is discussed amongst scholars from various disciplines the voices of consumers, the target-group of nudges, remain unheard. Since understanding their knowledge about n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 19 publications
9
50
1
6
Order By: Relevance
“…The related theme on ambivalent responsibility-participants stressing individual or parental responsibility for making healthy food choices on the one hand and the positive attitudes towards reducing store temptations on the other-was found across our qualitative data collected in different ways and across community and store settings. Furthermore, this ambivalent responsibility theme is in keeping with surveys showing broad support of statements stressing the individual responsibility for health while at the same time strongly supporting the idea of conducting health promoting interventions in public environments especially those targeting children [11, 42, 43]. This finding is also in line with studies identifying themes of individualization, self-control and self-responsibility in both consumer and food retailer discourses on healthy food choices [4447].…”
Section: Discussionsupporting
confidence: 79%
“…The related theme on ambivalent responsibility-participants stressing individual or parental responsibility for making healthy food choices on the one hand and the positive attitudes towards reducing store temptations on the other-was found across our qualitative data collected in different ways and across community and store settings. Furthermore, this ambivalent responsibility theme is in keeping with surveys showing broad support of statements stressing the individual responsibility for health while at the same time strongly supporting the idea of conducting health promoting interventions in public environments especially those targeting children [11, 42, 43]. This finding is also in line with studies identifying themes of individualization, self-control and self-responsibility in both consumer and food retailer discourses on healthy food choices [4447].…”
Section: Discussionsupporting
confidence: 79%
“…Thereby, it is relevant to note that a majority of employees were positive about the nudge intervention. This aligns with prior research indicating that people are generally appreciative of nudges that help them perform health behaviours (Kroese et al, 2016;Junghans, Cheung, & De Ridder, 2015). Only a minority of 11% indicated to disapprove of the nudge intervention, which is low when placing this percentage in the context of nudge approval in general: a recent paper by Reisch and Sunstein (2016) indicated that 42% of their polled Europeans disapproved of the presented default nudges.…”
Section: Contributionssupporting
confidence: 83%
“…This research is among a small number of studies to explore the role of individual, household, and geographic characteristics for the approval of a range of nudges (Diepeveen et al ; Felsen, Castelo, and Reiner ; Hagman et al ; Jung and Mellers ; Junghans, Cheung, and de Ridder ; Petrescu et al ; Tannenbaum, Fox, and Rogers ). It complements recent findings on attitudes toward nudges (Jung and Mellers ) and contributes further insights into consumer responses to nudges (Reisch and Sunstein ).…”
Section: Description Of Nudges and Approval Rates By Countrymentioning
confidence: 99%